2016
DOI: 10.1161/atvbaha.115.306768
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Vasoreactivity, Apolipoprotein E, and the Risk of Dementia

Abstract: A bout 44 million people worldwide are living with dementia, and because of a rapidly aging population this number is predicted to nearly double every 20 years until 2050. 1,2 Consequently, the social and economic burden of dementia will increase enormously, unless preventive or curative measures can be established. Cardiovascular health is increasingly acknowledged as a key determinant in prevention of dementia, including Alzheimer disease (AD).3,4 Yet, the mechanism by which vascular damage leads to cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 51 publications
(57 reference statements)
0
31
1
Order By: Relevance
“…It has been established that cerebral hypoperfusion and increased pulsatility index (PI) are associated with a clinical diagnosis of AD . More promising (for early detection considerations) is recent evidence suggesting that changes in cerebral perfusion are present long before clinical symptoms of AD are manifest. This evidence is promising because cerebral perfusion is much easier to assess than Aβ accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that cerebral hypoperfusion and increased pulsatility index (PI) are associated with a clinical diagnosis of AD . More promising (for early detection considerations) is recent evidence suggesting that changes in cerebral perfusion are present long before clinical symptoms of AD are manifest. This evidence is promising because cerebral perfusion is much easier to assess than Aβ accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Two important mechanisms for maintenance of proper and continuous cerebral perfusion are local vasoreactivity and autonomous nervous system function. Cerebral vasoreactivity has indeed been found to be associated with the risk of developing dementia in the general population [ 6 ], but the role of autonomous nervous system function in the onset of dementia has been less well studied.…”
Section: Introductionmentioning
confidence: 99%
“…A dose-response association between APOE genotypes and ischemic stroke has been shown in a systemic review and meta-analysis. 31 Other studies have shown that APOE genotypes were associated with cerebral vasoreactivity 32 and central arterial stiffening. 33 These findings suggested that the interaction between APOE genotypes and cerebral vascular changes needs to be considered in the disease process to be related to both APOE and VRFs.…”
Section: Discussionmentioning
confidence: 99%